Hydroperoxide-mediated degradation of acetonitrile in the lithium–air battery - McNulty, RC; Jones, KD; Holc, C; Jordan, JW; Bruce, PG; Walsh, DA; Newton, GN; Lam, HW; Johnson, LR (Wiley, 2023)
Understanding and eliminating degradation of the electrolyte solution is arguably the major challenge in the development of high energy density lithium–air batteries. The use of acetonitrile provides cycle stability comparable to current state-of-the-art glyme ethers and, while solvent degradation has been extensively studied, no mechanism for acetonitrile degradation has been proposed. Through the application of in situ pressure measurements and ex situ characterization to monitor the degradation of acetonitrile in the lithium–air battery, a correlation between H2O concentration within the cell and deviation from the idealized electron/oxygen ratio is revealed. Characterization of the cycled electrolyte solution identifies acetamide as the major degradation product under both cell and model conditions. A new degradation pathway is proposed that rationalizes the formation of acetamide, identifies the role of H2O in the degradation process, and confirms lithium hydroperoxide as a critical antagonistic species in lithium–air cells for the first time. These studies highlight the importance of considering the impact of atmospheric gases when exploring lithium–air cell chemistry and suggest that further exploration of the impact of hydroperoxide species on the degradation in lithium–air cells may lead to identification of more effective electrolyte solvents.